Save Stan Simulation Saturday - Planning and Implementing an Interprofessional Simulation Day - Sharla King; Dawn Ansell; Colette Foisy-Doll; Sam Magus; Elaine Greidanus; Kinga Kowalewska-Grochowska (Association of American Medical Colleges, 2013)
Abstract Save Stan Simulation Saturday is a full-day educational event encompassing a series of interprofessional health team simulations supplemented by additional communication and team educational activities. This event provides students from various health disciplines with an opportunity for collaborative experiential learning in realistic, risk-free health and community-care settings. The simulations span the entire care continuum and include postoperative, home care, continuing care, prenatal, sports medicine, and team interviews in diverse clinical and community settings. Simulation modalities include mannequins, standardized patients, and virtual worlds. Complementing the simulation exercises are additional educational activities centering on teamwork and communication and using innovative teaching approaches that range from visual and performing arts to multimedia presentations and electronic charting. The focus of all activities in this resource is on interprofessional communication, collaboration, and role clarification. The resource concentrates on three types of activities: main simulations, mini-simulations, and teamwork and communication activities. This resource has been delivered to over 350 students and has provided facilitation opportunities for more than 100 educators from eight organizations. Preliminary analysis of the data shows that this event has a significant impact on students' appreciation of other discipline perspectives as well as on their knowledge of their own role and the roles of others, including role overlaps.